2020
DOI: 10.2169/internalmedicine.3435-19
|View full text |Cite
|
Sign up to set email alerts
|

Two Cases of Primary Human Parainfluenza Virus 1 Pneumonia in Which Bronchoalveolar Lavage Fluid Yielded Human Parainfluenza Virus 1

Abstract: Two patients, a 76-year-old woman and 66-year-old woman, presented to our hospital with symptoms of lower respiratory tract infection. Both patients showed chest imaging findings of bilateral ground-glass opacities and consolidations. We initially suspected these patients of having influenza-associated pneumonia and cryptogenic organizing pneumonia, respectively, and performed bronchoalveolar lavage, but only human parainfluenza virus-1 infection was detected by multiplex polymerase chain reaction testing. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…To the best of our knowledge, these patients are the rst reported cases of eosinophilic pneumonia caused by parain uenza virus. Basic studies have shown that eosinophils in guinea pig BAL uid are also increased by infection with parain uenza virus [18], and in two case reports of parain uenza virus pneumonia, the eosinophil fraction in BAL uid was slightly elevated [19]. Thus, reports of eosinophilic airway in ammation due to parain uenza infection are not uncommon and are consistent with the causes of eosinophilic pneumonia, as in the cases in this study.…”
Section: Discussionsupporting
confidence: 88%
“…To the best of our knowledge, these patients are the rst reported cases of eosinophilic pneumonia caused by parain uenza virus. Basic studies have shown that eosinophils in guinea pig BAL uid are also increased by infection with parain uenza virus [18], and in two case reports of parain uenza virus pneumonia, the eosinophil fraction in BAL uid was slightly elevated [19]. Thus, reports of eosinophilic airway in ammation due to parain uenza infection are not uncommon and are consistent with the causes of eosinophilic pneumonia, as in the cases in this study.…”
Section: Discussionsupporting
confidence: 88%
“…Although there have been reports of cases of eosinophilic pneumonia with a marked elevation of BAL eosinophil fraction in influenza virus infection and COVID-19 [24][25][26], there are no reports of eosinophilic pneumonia caused by parainfluenza virus. There has been a case report of parainfluenza virus pneumonia; however, the increase of BAL eosinophils was mild and not eosinophilic pneumonia [27]. It is likely that there are many more cases of eosinophilic pneumonia caused by respiratory viral infections in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…28 Transbronchial lung biopsy from two immunocompetent patients showed an infiltration of neutrophils, macrophages, lymphocytes, and fibrin exudation. 5 These observations suggest that the disease severity of hPIVs-associated pneumonia might relate to the dysregulation of host-virus immune response. PB parameters, which are easily accessible and reflect the immune system status, are valuable for disease severity evaluation and the subsequent clinical management of the patients.…”
Section: Pcamentioning
confidence: 99%
“…It was generally thought that hPIVs‐induced pneumonia could be attributed to high levels of viral replication, resulting in a specific attack against target cells 4 . However, histopathology of pneumonia caused by hPIVs, which had been studied in more detail, was characterized by obstruction of the small airways by inflammatory cell debris, edema, and external compression of the bronchioles from hyperplastic lymphoid follicles 5 . Thus, disease severity is not only due to viral infection but it is strongly influenced by the characteristics of the host immune response to hPIVs infection.…”
Section: Introductionmentioning
confidence: 99%